Preparation characterization and non-isothermal decomposition kinetics of different carbon nitride sheets - M. Elshafie; S.A. Younis; P. Serp; E.A.M. Gad (Egyptian Journal of Petroleum)
Three series of graphitic carbon nitride g-C3N4 namely bulk (BCN), sulfur-doped (SCN) and thin layer (TCN) sheets are prepared using urea precursor under a microwave thermal pyrolysis. Several analytical techniques are used to characterize the obtained g-C3N4 products namely, XRD, FTIR, TEM, SPR, DRS, and BET. To study the thermal stability of the synthesized graphite-like materials, the solid-state decomposition kinetics of BCN, SCN and TCH products were investigated using TGA. The energy of activation Ea and the frequency factor A. Decomposition pathway were investigated using four mathematical methods and 35 mechanisms (g(α)) models. The computed thermodynamic parameters proved that the thermal deformation mechanism of g-C3N4 sheets depends on the diffusion process. The SCN and TCN sheets are less order in the deformation arrangement and possess higher entropy (ΔS°). The arrangement in the 2nd deformation stage of TCN is higher than in the dehydration stage. Keywords: Graphitic carbon nitride, Non-isothermal kinetics